The unexpected : narrative temporality and the philosophy of surprise - Currie, Mark, 1962- (Frontiers of theory., 2013)
"Focusing on surprise, spontaneous eruption and the unforeseeable, The Unexpected argues that stories help us to reconcile what we expect with what we experience. Though narrative is often understood a recapitulation of past events, the book argues that the unexpected and the future anterior, a future that is already complete, are guiding ideas for new understandings of the reading process. It also points beyond that to some of the key temporal concepts of our epoch, of unpredictability, the event, the untimely and the messianic. The Unexpected is an important intervention in narratology and a striking general argument about the cultural significance of surprise. The enquiry is developed by a range of new readings in philosophy and theory, as well as of Sarah Waters's Fingersmith, Kazuo Ishiguro's Never Let Me Go and Julian Barnes's The Sense of an Ending."--